Ultrasound-Guided Regional Anesthesia for Pediatric Burn Reconstructive Surgery: A Prospective Study. Issue 3 (May 2016) - Shank, Erik S.; Martyn, Jeevendra A.; Donelan, Mathias B.; Perrone, Anthony; Firth, Paul G.; Driscoll, Daniel N.
Abstract : Pediatric patients face multiple reconstructive surgeries to reestablish function and aesthetics postburn injury. Often, the site of the harvested graft for these reconstructions is reported to be the most painful part of the procedure and a common reason for deferring these reconstructive procedures. This study in pediatric burn patients undergoing reconstructive procedures examined the analgesia response to local anesthetic infiltration versus either a single ultrasound-guided regional nerve block of the lateral femoral cutaneous nerve (LFCN) or a fascia iliaca compartment block with catheter placement and continuous infusion. Nineteen patients were randomized to one of three groups (infiltration, single-shot nerve block, or compartment block with catheter) and received intraoperative analgesia intervention. Postoperatively, visual analog scale pain scores were recorded—for pain at the donor site—every 4 hours while awake—for 48 hours. This nonparametric data was analyzed using a two-way ANOVA, Friedman's test, and Kruskal–Wallis test, with significance determined at P < 0.05. The analysis demonstrated that the patients in the regional anesthesia groups were significantly more comfortable over the 48 hour hospital course than the patients in the control group. The patients receiving a single-shot block of the LFCN were more comfortable on postoperative day (POD) 0 while the catheter patients were more comfortable on POD 1 and POD 2. There was not a statistically significant difference in opioid requirements in any group. Regional anesthetic block of the LFCN, with or without catheter placement, provides an improved postoperative experience for the pediatric patient undergoing reconstructive surgery with lateral/anterolateral skin graft versus local anesthesia infiltration of donor site. For optimal comfort throughout the postoperative period, an ultrasound-guided block with continuous catheter may be beneficial.